2015
DOI: 10.1021/es505521w
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Shows That Low-Energy Anaerobic−Aerobic Treatment Reactors Reduce Antibiotic Resistance Gene Levels from Domestic Wastewater

Abstract: Effective domestic wastewater treatment is among our primary defenses against the dissemination of infectious waterborne disease. However, reducing the amount of energy used in treatment processes has become essential for the future. One low-energy treatment option is anaerobic-aerobic sequence (AAS) bioreactors, which use an anaerobic pretreatment step (e.g., anaerobic hybrid reactors) to reduce carbon levels, followed by some form of aerobic treatment. Although AAS is common in warm climates, it is not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(67 citation statements)
references
References 46 publications
5
62
0
Order By: Relevance
“…These findings reinforce the observations of the previously mentioned study that utilized qPCR to show that particular ARGs were better removed at thermophilic temperatures while others were better removed under mesophilic conditions [57]. Yet another study employing metagenomics sought to evaluate anaerobic treatment of wastewater as compared to both aerobic and low-energy anaerobic-aerobic treatment [66]. Results revealed that although all three of the methods greatly reduced total ARG abundance, low-energy anaerobic-aerobic treatment showed the most promising results.…”
Section: The Effect Of Anaerobic Digestion On Argssupporting
confidence: 83%
“…These findings reinforce the observations of the previously mentioned study that utilized qPCR to show that particular ARGs were better removed at thermophilic temperatures while others were better removed under mesophilic conditions [57]. Yet another study employing metagenomics sought to evaluate anaerobic treatment of wastewater as compared to both aerobic and low-energy anaerobic-aerobic treatment [66]. Results revealed that although all three of the methods greatly reduced total ARG abundance, low-energy anaerobic-aerobic treatment showed the most promising results.…”
Section: The Effect Of Anaerobic Digestion On Argssupporting
confidence: 83%
“…The intermediate products, such as hydroxyl radical and hydrogen peroxide produced by inefficient catalysis of oxygen reduction reactions (Yuan et al, 2015b), may cause oxidative stress of ARBs and damage of ARGs. It has recently been reported that the combination of anaerobic and aerobic treatment remove more ARGs than an anaerobic process alone (Christgen et al, 2015). Moreover, the fate of ARBs and ARGs in other types of BES that focus on biosynthesis or water recovery may differ from that in MFCs and MECs.…”
Section: Perspectivesmentioning
confidence: 99%
“…The removal rate and efficiency of ARGs encoding tetracycline resistance could be increased with increased temperature of the digester (Diehl and LaPara, 2010). Anaerobic digestion was also used as pre-treatment for aerobic stirred tank reactors and noticeably enhanced the removal of a variety of ARGs (Christgen et al, 2015). While these prior studies demonstrated that ARBs and ARGs can be reduced under some circumstances by anaerobic digesters, there remains a knowledge gap with respect to the removal mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on a WWTP in Hong Kong clearly associates Gordonia,a filamentous bacterium that produces mycolic acid, with seasonal foaming episodes, and also indicates that this problem is associated with markers for nitrogen metabolism (Jiang et al, 2016). Workers have also studied antibiotic-resistant genes in WWTP reactors (Christgen et al, 2015), and their mobility among organisms within plants (Munck et al, 2015;Wang, et al, 2013). Other works are illuminating capacities to decompose pharmaceuticals (Balcom et al, 2016) and phenol (Silva et al, 2012) in wastewaters.…”
Section: Introductionmentioning
confidence: 99%